2010
DOI: 10.2196/jmir.1549
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Health Data for Better Outcomes on PatientsLikeMe

Abstract: BackgroundPatientsLikeMe is an online quantitative personal research platform for patients with life-changing illnesses to share their experience using patient-reported outcomes, find other patients like them matched on demographic and clinical characteristics, and learn from the aggregated data reports of others to improve their outcomes. The goal of the website is to help patients answer the question: “Given my status, what is the best outcome I can hope to achieve, and how do I get there?”ObjectiveUsing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
428
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 558 publications
(447 citation statements)
references
References 30 publications
(34 reference statements)
7
428
1
6
Order By: Relevance
“…Privacy concerns associated with sharing health information online include possible discrimination by the employers, insurance companies, friends, or family of those who post [8]. There are also concerns about "potential 'data intruders'…with motivations ranging from personal research, genealogy, ancestry, forensic purposes or use in marketing, insurance, or employment decisions" [8].…”
Section: Potential Privacy Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Privacy concerns associated with sharing health information online include possible discrimination by the employers, insurance companies, friends, or family of those who post [8]. There are also concerns about "potential 'data intruders'…with motivations ranging from personal research, genealogy, ancestry, forensic purposes or use in marketing, insurance, or employment decisions" [8].…”
Section: Potential Privacy Risksmentioning
confidence: 99%
“…There are also concerns about "potential 'data intruders'…with motivations ranging from personal research, genealogy, ancestry, forensic purposes or use in marketing, insurance, or employment decisions" [8]. In the research context, institutional review boards (IRBs) may be concerned about how information from online health communities is being collected and used as they strive to protect research participants from invasion of privacy [18].…”
Section: Potential Privacy Risksmentioning
confidence: 99%
“…cancer) are shown to exchange information online twice more often than patients of nonchronic diseases . Also, patients who actively seek advice online and exchange words of social encouragement are shown to result in better health outcome (Wicks et al, 2010). Therefore, by supporting cancer survivors to take advantage of the communication innovation by using the 'grassroots participatory model,' the management of patients' cancer across their cancer continuum can greatly assist the patient.…”
Section: Characteristics Of Communication Innovation and Its Light Anmentioning
confidence: 99%
“…Patients can leverage their discovered knowledge en masse to find and discuss possible avenues of treatment. An internal survey within the site concluded that 12% of the patients changed their physician's opinion about their course of treatment through information they received on the website [6].…”
Section: Non-physician-specific Networking Sitesmentioning
confidence: 99%
“…The rate limiting step to this empowerment is access to the technology however. Reducing power distances to patients have shown to improve patient confidence in starting, stopping, or making changes to treatment regimens [6].…”
Section: Effects On the Doctor-patient Relationshipmentioning
confidence: 99%